Research progress of Traditional Chinese Medicine acupoint application in the treatment of constipation after stroke (中药穴位贴敷治疗卒中后便秘的研究进展) - YANG Shuhui (杨淑慧); ZHANG Ran (张然); GENG Qingwen (耿庆文); ZHOU Dengfang (周登芳); TANG Ling (唐玲) (Association of Integrative Nursing, 2021)
Constipation is a common complication after stroke, affecting the prognosis and patient's quality of life. Traditional Chinese Medicine (TCM) acupoint application is an effective external treatment in the treatment of constipation after stroke. This paper summarized the basic theory of TCM acupoint application, selection of Chinese herbal medicine, selection of acupoint, application of dressing medium, timing of using application, in order to provide reference for development and new thoughts in TCM acupoint application for constipation after stroke. (便秘是脑卒中常见的并发症, 严重影响卒中患者的生活质量和预后。中药穴位贴敷疗法在治疗卒中后便秘方面效果明显, 是中医外治法中的一种常用治疗方法。本文主要总结了中药穴位贴敷的基础理论、药物的选择、穴位的选择、贴敷介质的使用、贴敷的时机等内容, 旨在为中药穴位贴敷治疗卒中后便秘提供新的思路, 从而促进中医外治法更好地应用于临床。)